Implementasi Kebijakan Penyediaan Lajur Khusus Sepeda Di Provinsi DKI Jakarta - Desy Ilmiawati; Evi Satispi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to analyze the policy implementation of DKI Jakarta Governor Regulation Number 128 of 2019 related to the provision of special bicycle lanes in DKI Jakarta and the factors that influence it. This research is a type of empirical legal research, which examines the implementation of applicable legal regulations and their impact on society. The method used is descriptive with a qualitative approach. The results of this study were analyzed through data reduction, presentation of analysis results in the form of narratives and conclusion making. The implementation of DKI Jakarta Governor Regulation Number 128 of 2019 on the implementation of special bicycle lanes in DKI Jakarta is carried out by the DKI Jakarta Provincial Transportation Agency through the installation of traffic signs and markings for special bicycle lanes, as well as socialization efforts. However, in its implementation, there are several factors that play a role in difficulties and challenges. These factors include the lack of effective socialization by law enforcement officials, low public awareness and legal compliance with the rules of the special bicycle lane, and the indecisiveness of law enforcement by law enforcement officials against violations of these rules. Seeing that violations still occur due to the lack of strict law enforcement by law enforcement officials, it is recommended to make maximum efforts to increase compliance to the bicycle lane regulations. This aims to create a safe environment for bicycle lane users and improve traffic order in DKI Jakarta. Thus, the implementation of this regulation is expected to run more effectively and provide greater benefits to the community.